Review of the effects of seed priming for improving seed germination, seedling establishment and yield on several pulse crops - Urmita Garai; Sabyasaci Patra (Journal of Stress Physiology & Biochemistry)
Pulses are a unique type of crop due to their high content of vegetable protein, an important part of the human diet, and their major contribution to the cropping system through nitrogen fixation. A wide range of physiological deterioration that results in qualitative, quantitative, and economic losses occurs during the post-harvest storage of pulse crops. For pulse crop germination, growth, seedling establishment, and yield, the appropriate abiotic and biotic conditions are required. The article covers the seed priming approach, which can coordinate seed germination and increase vigor for better seedling establishment and productivity. Seed priming turns on metabolic pathways that break dormancy, prevent seeds from degrading, and boost overall resilience to biotic and abiotic stressors. The overall review provided in this paper describes how seed priming enhances pulse crop germination, seedling establishment, growth, and yield.